2000
DOI: 10.1523/jneurosci.20-17-06431.2000
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Characterization of an α4 Neuronal Nicotinic Acetylcholine Receptor Subunit Knock-Out Mouse

Abstract: Neuronal nicotinic acetylcholine receptors (nAChR) are present in high abundance in the nervous system (Decker et al., 1995). There are a large number of subunits expressed in the brain that combine to form multimeric functional receptors. We have generated an alpha(4) nAChR subunit knock-out line and focus on defining the behavioral role of this receptor subunit. Homozygous mutant mice (Mt) are normal in size, fertility, and home-cage behavior. Spontaneous unconditioned motor behavior revealed an ethogram cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
215
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(226 citation statements)
references
References 52 publications
(67 reference statements)
8
215
3
Order By: Relevance
“…222 These mice displayed increased level of anxiety (mostly in the elevated plus maze), as well as other characteristic such as poor motor learning and excessive locomotion activity, that was eliminated by low doses of nicotine injection. 222 The role of the a4-subunit in anxiety in a stressful setting was assessed by Ross et al 223 a4-KO mice show behavioral features consistent with heightened basal levels of anxiety and increased exploratory activity in stressful settings, 223 consistent with the reports of Labarca et al 222 Finally, as with deletion of the a4 and b4-subunit, chrnb3 KO mice showed altered anxiety-like behavior, when compared with WT, assessed by a series of behavioral tests. 224 Thus, in addition to their direct influence on NDrelated phenotypes, neuronal nAChRs genes may mediate predisposition to neuroticism, a personality trait that is a susceptibility factor for smoking.…”
Section: General Overviewmentioning
confidence: 55%
“…222 These mice displayed increased level of anxiety (mostly in the elevated plus maze), as well as other characteristic such as poor motor learning and excessive locomotion activity, that was eliminated by low doses of nicotine injection. 222 The role of the a4-subunit in anxiety in a stressful setting was assessed by Ross et al 223 a4-KO mice show behavioral features consistent with heightened basal levels of anxiety and increased exploratory activity in stressful settings, 223 consistent with the reports of Labarca et al 222 Finally, as with deletion of the a4 and b4-subunit, chrnb3 KO mice showed altered anxiety-like behavior, when compared with WT, assessed by a series of behavioral tests. 224 Thus, in addition to their direct influence on NDrelated phenotypes, neuronal nAChRs genes may mediate predisposition to neuroticism, a personality trait that is a susceptibility factor for smoking.…”
Section: General Overviewmentioning
confidence: 55%
“…No statistically significant differences were found in gait analysis or rotarod testing in MUT mice examined at 10-11 or 17-21 wk (SI Text). Separate cohorts of WT and MUT animals were assessed at two different age ranges by using a standardized ethological assay (22)(23)(24). At 6-9 wk, there was an increase in total rearing and a decrease in sifting and chewing (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Rotarod motor performance and gait testing were performed as described in SI Materials and Methods. Ethological assessments were carried out by using a rapid time-sampling behavioral checklist technique, as described (22,23). Ten MUT and 9-10 WT mice of each sex were used.…”
Section: Methodsmentioning
confidence: 99%
“…Healthy viable mice null for the a6 nicotinic subunit were provided by Dr Uwe Maskos at Institut Pasteur (Paris, France) (Champtiaux et al, 2002). Viable mice null for the a4 subunit were provided by Dr Henry Lester at the California Institute of Technology, with the permission of Dr John Drago (Ross et al, 2000). Mutant and WT mice were obtained from crossing heterozygous (HET) mice.…”
Section: Animalsmentioning
confidence: 99%
“…In contrast to our results, Cahir et al, (2011) reported that a4 KO and WT mice showed similar nicotine CPP at 0.5 mg/kg. Although the two studies used the same a4 KO and WT progenitors (Ross et al, 2000) and they were back-crossed to C57BL6 mice for at least 10 generations, the C57BL6 substrain used for back-crossing in the Cahir et al (2011) study was not reported. This is an important distinction, as critical behavioral differences between the various C57BL6 substrains (in particular with C57BL6/J, the substrain used in our studies) have been reported (Mulligan et al, 2008;Mekada et al, 2009;Matsuo et al, 2010).…”
Section: A6* Nachrs Subtypes In Nicotine Cppmentioning
confidence: 99%